ANALISIS PENYAJIAN ASET TIDAK BERWUJUD PADA LAPORAN KEUANGAN PERUSAHAAN GO PUBLIK (STUDI KASUS PERUSAHAN TERCATAT DI BEI TAHUN 2012 YANG SUDAH MENERBITKAN LAPORAN KEUANGAN PADA APRIL 2013) - Utomo, Budi (Jurnal Akuntansi AKUNESA, 2014)
In accordance with PSAK 1 Effective January 1, 2011, requires that every company fairly present the financial statements. Based on previous research which suggests that the current intangible assets are concerned, therefore, this study wanted to find out whether intangible assets are presented in the financial statements in accordance with PSAK 1. Research objects in use is 306 financial reports of companies listed on the Stock Exchange in 2012 which was published in April 2013 financial reports, this study used a qualitative descriptive method to analyze the presentation of intangible assets in the statements of financial position and notes to the financial statements. The results showed that the majority of companies are still not present or disclose information intangible assets.Keywords: PSAK 1 revisi 2009, intangible assets, financial statements.